Between English and Spanish: A Linguistic Study of Code-switching in Selena Gomez’s Song “Ojos Tristes” - Balqis, Aura Savinka; Gultom, Elfa Salsabila; Rangkuti, Rahmad syah (Journal of English Language and Education, 2026)
This study explores how Selena Gomez intentionally switches between English and Spanish in her song "Ojos Tristes" to deepen emotional impact and express her cultural identity. While bilingual music has gained more attention from researchers, there’s still a need to better understand the ways artists use language switching creatively in popular American music today. By closely analyzing the lyrics using established theories on code-switching, the study highlights three types switching between sentences, within sentences, and small inserted phrases that serve specific emotional and cultural purposes. The findings show that English tends to express calm, reasoned feelings, whereas Spanish conveys more personal and heartfelt emotions, reflecting Gomez’s blend of two cultures. Ultimately, the research shows that code-switching here isn’t random but a thoughtful artistic choice that challenges single-language expectations and celebrates the richness of bilingual expression in mainstream music.